1995
DOI: 10.1093/brain/118.3.629
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of gyration, heterotopias, tuberous sclerosis, focal cortical dysplasia, microdysgenesis, dysembryoplastic neuroepithelial tumour and dysgenesis of the archicortex in epilepsy: Clinical, EEG and neuroimaging features in 100 adult patients

Abstract: Cerebral cortical dysgenesis (CD) is a heterogeneous disorder of cortical development and organization commonly associated with epilepsy, with a variety of subtypes. We reviewed the clinical, EEG and neuroimaging features in 100 adult patients with CD. There were 39 men and 61 women with a median age of 27 years (range 15-63 years). All patients were referred because of medically refractory epilepsy. Median age at seizure onset was 10 years (range 3 weeks to 39 years); in 30 patients, onset was in adulthood. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
259
3
6

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(292 citation statements)
references
References 1 publication
23
259
3
6
Order By: Relevance
“…This widespread cortical malformation corresponded well to a subtype, macrogyria/polymicrogyria with neuronal cleft, in the classification of Raymond et al [16]. However, we could not found the previous report about the reverse of the gray and white matter.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…This widespread cortical malformation corresponded well to a subtype, macrogyria/polymicrogyria with neuronal cleft, in the classification of Raymond et al [16]. However, we could not found the previous report about the reverse of the gray and white matter.…”
Section: Discussionsupporting
confidence: 64%
“…Clinical features of them were also different between the patients. Some classifications of cortical dysplasia were proposed as based on the findings of neuroimaging and/or histological characteristics [1,2,3,6,11,16]. However, it may be difficult to classify into one of subtypes in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On MRI, six children showed the evidence of focal cortical dysplasia (Raymond et al, 1995); four children had multiple cortical tubers; three children had a brain tumor; one child each had a solitary tuber and focal ulegyria. In the remaining two children, MRI was normal but FDG PET scan showed cortical regions with glucose hypometabolism in the presumed epileptic hemisphere.…”
Section: Patientsmentioning
confidence: 99%
“…Malformations of cortical development constitute 10-50% of pediatric epilepsy cases being evaluated for surgery and 4-25% of adult cases of intractable epilepsy. 103,136 Wolf and Wiestler 135 reported a frequency of 18% for cortical dysplasia in surgical specimens obtained in a series of 216 adult patients with intractable epilepsy. In contrast, in pediatric patients with refractory epilepsy who had undergone resection, Jay et al 54 reported a 30% frequency of FCD, whereas Farrell et al 36 reported a 39% frequency of FCD.…”
mentioning
confidence: 99%